Do we need 5-FU in addition to cisplatin for chemoradiation of locally advanced head-and-neck cancer?. (June 2016) - Rades, Dirk; Seidl, Daniel; Janssen, Stefan; Bajrovic, Amira; Hakim, Samer G.; Wollenberg, Barbara; Schild, Steven E.
Highlights: Cisplatin alone appeared associated with fewer adverse events than cisplatin plus 5-FU. Cisplatin alone appeared to result in better overall survival than cisplatin plus 5-FU. Chemoradiation with cisplatin alone may be preferable to cisplatin plus 5-FU. Summary: Objectives: To compare chemoradiation with cisplatin alone or cisplatin plus 5-FU for locally advanced squamous cell carcinoma of the head-and-neck (SCCHN). Materials and methods: The outcomes of 142 patients who received chemoradiation with cisplatin alone for locally advanced SCCHN were retrospectively compared to 170 patients who received cisplatin plus 5-fluorouracil (5-FU). The outcomes compared included loco-regional control (LRC), metastases-free survival (MFS), overall survival (OS) and adverse events. Results: Although patients who received cisplatin alone had a significantly worse performance status, 81% of these patients completed planned chemotherapy compared to 73% of patients in the cisplatin plus 5-FU group ( p  = 0.18). Radiotherapy breaks >1 week were necessary in 14% and 23% of patients, respectively ( p  = 0.09). The 5-year LRC rates were 69% after cisplatin alone and 68% after cisplatin plus 5-FU ( p  = 0.71). The 5-year MFS rates were 72% and 62%, respectively ( p  = 0.37), and 5-year OS rates were 60% and 45%, respectively ( p  = 0.066). On multivariate analysis, cisplatin alone was significantly associated with improved OS (RR 1.35; 95%-CI 1.09–1.69; p  = 0.006). Nausea/vomiting, pneumonia/sepsis and late adverse events occurred more common in the cisplatin plus 5-FU group. Conclusion: Given the limitations of a retrospective study, chemoradiation with cisplatin alone appeared associated with fewer adverse events and better OS than with cisplatin plus 5-FU in patients with locally advanced SCCHN. Thus, 5-FU in addition to cisplatin may be omitted for these patients. A randomized trial is warranted to confirm these findings.